Recent advances on the transport of microplastics/nanoplastics in abiotic and biotic compartments - Huang, D.; Chen, H.; Shen, M.; Tao, J.; Chen, S.; Yin, L.; Li, R.
Plastics enter the environment and break up into microplastics (MPs)and even nanoplastics (NPs)by biotic and abiotic weathering. These small particles are widely distributed in the environmental media and extremely mobile and reactive, easily suspending in the air, infiltrating into the soil, and interacting with biota. Current research on MPs/NPs is either in the abiotic or biotic compartments, with little attention paid to the fact that the biosphere as a whole. To better understand the complex and continuous movement of plastics from biological to planetary scales, this review firstly discusses the transport processes and drivers of microplastics in the macroscopic compartment. We then summarize insightfully the uptake pathways of MPs/NPs by different species in the ecological compartment and analyze the internalization mechanisms of NPs in the organism. Finally, we highlight the bioaccumulation potential, biomagnification effects and trophic transfer of MPs/NPs in the food chain. This work is expected to provide a meaningful theoretical body of knowledge for understanding the biogeochemical cycles of plastics.
Keywords: INTERNALIZATION; MACROSCOPIC TRANSPORT; PLASTICS; TROPHIC TRANSFER